Pemberdayaan BATAKUM (Budaya Wisata Megalithikum) Melalui Pelatihan Digitalisasi Karang Taruna Desa Gunung Megang - Siti Aminah; Fameira Dhiniati; Barrorotul Azizah (Pusat Riset dan Inovasi Nasional, 2024)
The aim of this activity is to empower the youth of Gunung Megang village by promoting megalithic tourism culture and traditional food in Gunung Megang village by carrying out innovation and digitalization training. The community has a strong desire for entrepreneurship, so it needs to be facilitated to increase the productivity of crafts and the number of tourist visits. Efforts to increase these skills cannot be carried out independently by the people of Gunung Megang village, so the role of academics is to develop the traditional snacks and tourism industries. This activity has the urgency of encouraging a group of people to be able to adapt to technology. Currently, the people of Gunung Megang village have a lot of promotion of tourism attractions and local snacks, but the marketing of craft industry products and tourism potential has not been spread through advanced technology because it is still limited to direct information. Community service is produced as a result of more modern food packaging and social media accounts in the form of Instagram, TikTok, and Facebook, which are expected to become media for promoting tourism resources in Gunung Megang village.